Peningkatan Pemahaman Sosialisasi Tentang Identitas Nasional Melalui Kegiatan Pencegahan Bullying Pada Anak Sekolah Di MTSN 04 Kota Padang - Harniawati Harniawati; Elwidarifa Marwenny; Virly Dwi Febriani; Dipa Aditya; Mizia Yolanda; Zahra Mutia Putri; Prisma Alrezky; Rike Safrianti; Kaka Rolanda (GLOBAL SCIENTS PUBLISHER, 2025)
Law Study Program at Dharma Andalas University group 2 citizenship course carried out observation activities in the form of Increasing Understanding of Socialization of National Identity Through Bullying Prevention Activities for School Children at MTSN 04 Padang City which aims to increase awareness of MTSN 04 Padang City students about the importance of preventing bullying in the school environment. This socialization is designed to provide students with an understanding of the negative impacts of bullying, both physically, emotionally, and socially, which can disrupt the harmony of the learning process. Through this activity, students will be given education about the definition of bullying, its types, and how to overcome it. In addition, this socialization is expected to build empathy and tolerance among students so that a safe, comfortable, and harmonious school environment is created. With this socialization, it is hoped that MTSN 04 Padang students will be able to develop an attitude of mutual respect, uphold humanitarian values, and play an active role in creating a school environment free from bullying in order to support successful learning.